Does Production Specialization Have an Impact on the Financial Efficiency of Very Small Farms? - Agnieszka STRZELECKA; Danuta ZAWADZKA (Communications of International Proceedings, 2020)
The main goal of the research was to answer the question whether the type of production affects the financial efficiency of very small farms. The subjective scope covered very small farms in Poland. The basic source of data were statistics collected as part of the system for collecting and using farm accountancy data - Farm Accountancy Data Network (Polish FADN). Very small farms were identified based on the criterion of their economic size (economic size class: very small, from 4,000 to 8,000 EUR SO). Data for the years 2013-2017 were used for the analysis. The research showed, among others, that regardless of the direction of production, very small farms included in the analysis were characterized by a high significance of fixed assets in the structure of assets, a high degree of self-financing of agricultural activity and a high cost of production. It was also found that units focused on permanent crops had the highest production value and the highest level of costs. In turn, the highest level of agricultural income was characteristic of units focused on field crops, with the entire income coming from operating subsidies. In 2017, financial efficiency in all considered types of very small agricultural holdings decreased in relation to 2013. The lowest financial efficiency in relation to the assets and equity involved was found in non-specialized farms and units focused on the production of herbivorous animals. The obtained results also proved the significant role of external financial support in creating the level of agricultural income of very small farms.
Keywords: very small farm; farm income; ROA; ROE; ROS; FADN; Poland.